2015
DOI: 10.1098/rspb.2015.0864
|View full text |Cite
|
Sign up to set email alerts
|

What you feel is what you see: inverse dynamics estimation underlies the resistive sensation of a delayed cursor

Abstract: How our central nervous system (CNS) learns and exploits relationships between force and motion is a fundamental issue in computational neuroscience. While several lines of evidence have suggested that the CNS predicts motion states and signals from motor commands for control and perception (forward dynamics), it remains controversial whether it also performs the 'inverse' computation, i.e. the estimation of force from motion (inverse dynamics). Here, we show that the resistive sensation we experience while mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 44 publications
(70 reference statements)
4
41
2
Order By: Relevance
“…Recent studies have reported effects of delayed visual feedback on perception, including increased mass (Honda et al 2013) or resistance (Takamuku and Gomi, 2015), that are suggestive of a mechanical system representation. The anecdotal verbal responses of our participants that the paddle is “harder to maneuver,” “sluggish,” or “mechanical” are consistent with this view and with previous reports (Smith, 1972; Vercher and Gauthier, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have reported effects of delayed visual feedback on perception, including increased mass (Honda et al 2013) or resistance (Takamuku and Gomi, 2015), that are suggestive of a mechanical system representation. The anecdotal verbal responses of our participants that the paddle is “harder to maneuver,” “sluggish,” or “mechanical” are consistent with this view and with previous reports (Smith, 1972; Vercher and Gauthier, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…None of the previous studies that linked the reported effects of delayed visual feedback to a mechanical system representation (Sarlegna et al 2010; Honda et al 2013; Takamuku and Gomi, 2015; Leib et al 2017) examined them in the context of different movement frequencies or velocities. Because a mechanical system is essentially a frequency-dependent gain together with a phase shift, evaluating the frequency dependence of the representation is critical for distinguishing between the two representations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was suggested that the misalignment between the hand and the cursor is interpreted as a mechanical load of mass (the cursor) with a spring and a damper that connects between the hand and the cursor. This model was used to explain the changes in grip forces accompanied with delayed visual feedback (Sarlegna et al, 2010), the changes in resistive sensation following adaptation to visuomotor delay (Takamuku and Gomi, 2015), and the generalization between adapting to a visuomotor delay or to a mechanical system between the hand and the cursor (Leib et al, 2017). In addition, representation of mechanical system also explains the changes in movements after adapting to force field (Wang et al, 2001).…”
Section: Adaptation and Representation Of Visuomotor Delaymentioning
confidence: 99%